Study on the Effect of flour glue additive to reduce the gypsum curing time and improve the physical and mechanical properties of wood gypsumboard made from poplar particles and canola stem wastes - Hossein Rangavar (Regional Information Center for Science and Technology (RICeST), 2015)
One of the major problems in wood gypsum particleboard production, faster hydration and thus reducing its physical and mechanical properties. In order to increase the curing time of gypsum, was used from flour glue in wood gypsum particleboard production by using of canola wastes and poplar particles wood. To assess the time of setting of gypsum, the Vicat Needle was used based on the ASTM C191. For this purpose, pure gypsum paste and the pastes with ratios of 0, 0.1, 0.2, 0.3, 0.4 and 0.5 % flour glue to dried gypsum were settled in the mentioned device, then the setting time was determined. Thus amount 0.1% flour glue was selected on the manufacturing of wood gypsum particleboard. To evaluate the effects of flour glue and canola straw wastes on the physical and mechanical properties wood gypsum particleboard, two levels of flour glue (0 and 0.1 %) compared to the mass of the gypsum and the amount of canola straw wastes in 5 levels including (0, 25, 50, 75 and 100%) compared to the mass of poplar particles wood as a research variable factors were considered. Density of boards was 0.9 gr/cm3 and their thickness was 16 mm. The test specimens were prepared for measuring their physical and mechanical properties according to EN standard. Results obtained showed, flour glue lead to increase in gypsum hydration time and improved all of the physical and mechanical properties of wood gypsum particleboard. Also using of canola stem wastes increased value of water absorption & thickness swelling at 2 and 24 hours immersion. Flexural strength and modulus of elasticity of the boards were increase, up to 25% canola wastes compared with dry mass of poplar particles wood, however internal bond of the boards were decreased by the increasing the amount of the canola wastes.